Investigating the Role of English as a Foreign Language Learners’ Academic Motivation and Language Mindset in Their Grit: A Theoretical Review - Liu, Yiran (Frontiers in Psychology, 2022)
This review made a critical attempt to examine the studies on the role of English as a foreign language (EFL) learners’ academic motivation and growth mindsets in their grit. Some investigations have been done on the role of academic motivation in learner grit. However, a significant positive correlation between academic motivation and grit has been approved in related studies. The related literature review justified the results by broaden-and-build and expectancy-value theories. The related literature has shown that grittier learners persist in doing tasks, and developing their intrinsic motivation. Furthermore, the related literature has approved the effect of learners’ language mindset on their grit. In other words, learners with a growth mindset are persistent, and they devote their time to their performance. Finally, the pedagogical implications are expanded to promote the quality of language learning. This review also provides some suggestions for further research to illuminate our perspectives over motivation, mindset, and their interactions with each other.